Logic, rationality, and interaction : 6th International Workshop, LORI 2017, Sapporo, Japan, September 11-14, 2017, Proceedings /: 6th International Workshop, LORI 2017, Sapporo, Japan, September 11-14, 2017, Proceedings. (2017) - Unknown
No abstract available